Comparative genomics and transcriptome analysis reveals potential pathogenic mechanisms of Microdochium paspali on seashore paspalum - Jin, Peiyuan; Kong, Yixuan; Zhang, Ze; Zhang, Huangwei; Dong, Yinglu; Lamour, Kurt; Yang, Zhimin; Zhou, Yuxin; Hu, Jian (Frontiers in Microbiology, 2023)
The sparse leaf patch of seashore paspalum (Paspalum vaginatum Sw.) caused by Microdochium paspali seriously impacts the landscape value of turf and poses a challenge to the maintenance and management of golf courses. Little is known about the genome of M. paspali or the potential genes underlying pathogenicity. In this study, we present a high-quality genome assembly of M. paspali with 14 contigs using the Nanopore and Illumina platform. The M. paspali genome is roughly 37.32 Mb in size and contains 10,365 putative protein-coding genes. These encompass a total of 3830 pathogen-host interactions (PHI) genes, 481 carbohydrate-active enzymes (CAZymes) coding genes, 105 effectors, and 50 secondary metabolite biosynthetic gene clusters (SMGCs) predicted to be associated with pathogenicity. Comparative genomic analysis suggests M. paspali has 672 species-specific genes (SSGs) compared to two previously sequenced non-pathogenic Microdochium species, including 24 species-specific gene clusters (SSGCs). Comparative transcriptomic analyses reveal that 739 PHIs, 198 CAZymes, 40 effectors, 21 SMGCs, 213 SSGs and 4 SSGCs were significantly up-regulated during the process of infection. In conclusion, the study enriches the genomic resources of Microdochium species and provides a valuable resource to characterize the pathogenic mechanisms of M. paspali.